Development of Table Tennis Learning Media Based on Android Applications - Melya Nur Herliana; Haikal Millah; Selly Purnama (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to develop a table tennis learning media based on an android application that is tested for its product feasibility and can be used in lectures both online and as a guide in offline lectures. The research carried out was only up to the development or development stage because the other purpose of this research was only to develop and produce a table tennis learning media product based on an android application called "B-PONG" (Basic Ping-Pong). Ping-Pong is another name for table tennis and is already popular among the public. The instrument used in this research is a questionnaire/questionnaire given to experts/experts to determine or assess eligibility according to the validator's expertise so that it is validated by 3 experts/experts including table tennis material experts, physical education learning media experts, technical and informatics experts. In addition, a questionnaire/questionnaire is also given for users (students) to get feedback from users. The results of product validation indicate that the table tennis learning media "B-Pong" is categorized as good and suitable for use in the learning process. The results of the response to the use of the table tennis learning media product "B-Pong" are also categorized as good. Based on the results of the three experts, and the product usability test, the table tennis learning media product "B-Pong" is said to be feasible and can be used in the table tennis learning process. The next research plan will test the effectiveness of the product so that it can be seen the effect of "B-Pong" media when used in the table tennis learning process